Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/mnras/stz2099
|View full text |Cite
|
Sign up to set email alerts
|

A contribution of star-forming clumps and accreting satellites to the mass assembly of z ∼ 2 galaxies

Abstract: We investigate the contribution of clumps and satellites to the galaxy mass assembly. We analysed spatially resolved HubbleSpace Telescope observations (imaging and slitless spectroscopy) of 53 star-forming galaxies at z ∼ 1–3. We created continuum and emission line maps and pinpointed residual ‘blobs’ detected after subtracting the galaxy disc. Those were separated into compact (unresolved) and extended (resolved) components. Extended components have sizes ∼2 kpc and comparable stellar mass and age as the gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 143 publications
19
57
0
Order By: Relevance
“…Moreover, the high gas fractions inducing clumping in turbulent high-redshift massive disks further enhance this effect (Bournaud et al 2015), increasing the level of CO excitation of distant main-sequence galaxies with respect to local Milky Way-like objects. In other words, the same mechanisms that we consider here as acting on global galaxy scales might well be in action in subgalactic massive clumps, effectively mimicking starburst environments (Zanella et al 2015(Zanella et al , 2019. This is also consistent with the results from LVG modeling, where the density of the collisionally excited gas is the term driving the high-J emission, given the fast deexcitation rates.…”
Section: The Spatial Distribution Of Sfr As the Driver Of The Propertsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the high gas fractions inducing clumping in turbulent high-redshift massive disks further enhance this effect (Bournaud et al 2015), increasing the level of CO excitation of distant main-sequence galaxies with respect to local Milky Way-like objects. In other words, the same mechanisms that we consider here as acting on global galaxy scales might well be in action in subgalactic massive clumps, effectively mimicking starburst environments (Zanella et al 2015(Zanella et al , 2019. This is also consistent with the results from LVG modeling, where the density of the collisionally excited gas is the term driving the high-J emission, given the fast deexcitation rates.…”
Section: The Spatial Distribution Of Sfr As the Driver Of The Propertsupporting
confidence: 87%
“…This trend could be explained by the availability of copious molecular gas at high redshift (Daddi et al 2010a;Tacconi et al 2010Tacconi et al , 2018Scoville et al 2017a;Riechers et al 2019;Decarli et al 2019;Liu et al 2019a), ultimately regulated by the larger accretion rates from the cosmic web (Kereš et al 2005;Dekel et al 2009a). Moreover, higher SFRs could be induced by an increased efficiency of star formation due to the enhanced fragmentation in gas-rich, turbulent, and gravitationally unstable high-redshift disks (Bournaud et al 2007(Bournaud et al , 2010Dekel et al 2009b;Ceverino et al 2010;Dekel & Burkert 2014), reflected on their clumpy morphologies (Elmegreen et al 2007;Förster Schreiber et al 2011;Genzel et al 2011;Guo et al 2012Guo et al , 2015Zanella et al 2019). IR-bright galaxies with prodigious SFRs well above the level of the MS are observed also in the distant Universe, but their main physical driver is a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Constraints on the timescales of physical processes: In addition to the two approaches described above, observations can also directly measure timescales for gas depletion (Kennicutt Jr 1998;Wong & Blitz 2002;Bigiel et al 2008), stellar winds (Sharp & Bland-Hawthorn 2010;Ho et al 2016), disk formation (Kobayashi et al 2007), bulge growth (Lang et al 2014;Tacchella et al 2015), black hole growth (Hopkins et al 2005) and more, albeit for limited samples of galaxies. On short timescales, a large body of work also exists studying GMC lifetimes (∼ 10 − 30 Myr) (Zanella et al 2019;Kruijssen et al 2019;Chevance et al 2020), measuring the extent to which this depends on environment, and the extent to which it is decoupled from galactic dynamics. Krumholz et al (2017) also find episodic starbursts lasting ∼ 5−10 Myr with intervals of ∼ 20−40 Myr in a ring around the Milky-Way's central molecular zone.…”
Section: Observational Constraints In Psd Spacementioning
confidence: 99%
“…Some observed clumps appear to be old: e.g., Guo et al (2012) found clump ages in the range 10 8 − 10 9 yr, Soto et al (2017) in the range 10 6 − 10 10 yr, Zanella et al (2019) in the range 10 6 −10 9 yr. The oldest end of these intervals is used to argue the longevity of the clumps.…”
Section: Clump Longevitymentioning
confidence: 99%